The chimpanzee children of Gombe : 50 years with Jane Goodall at Gombe National Park - Goodall, Jane, 1934- (Michael Neugebauer Publishing, 2014)
Jane Goodall introduces young readers to some of her favorite chimpanzees living in Gombe National Park, describing their behavior and family life.